Internal Control and Integrity in Preventing Village Financial Fraud: Pengendalian Internal dan Integritas dalam Mencegah Kecurangan Keuangan di Desa - Fitrilia, Dera Ika; Dwi Oktavia Rini, Dina (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Financial fraud in village fund management undermines public trust and development effectiveness. Specific Background: Strengthening internal control, moral integrity, and transparency is crucial to prevent fraudulent practices in village administrations. Knowledge Gap: Prior studies emphasize financial systems but overlook behavioral and ethical determinants of fraud prevention. Aims: This research investigates how human resource competence, internal control systems, and moral integrity affect fraud prevention in village financial management. Results: Findings show that internal audits, ethical leadership, and whistleblowing systems significantly reduce fraud tendencies. Novelty: The integration of moral sensitivity with institutional controls provides a multidimensional framework for preventing village-level corruption. Implications: Strengthening human resource training and fostering ethical culture are critical for sustainable village governance. Highlights: Ethical culture minimizes fraud in village finance. Internal control improves accountability. Whistleblowing enhances transparency and trust.